(untitled) (Global Journal of Medical Research, 2020)
This paper reviews the current accepted practice for high touch surface cleaning and disinfection to kill surface COVID-19 virus such that transmission risks are lowered. Surface cleaning and disinfecting is considered from a workplace perspective, in a non-healthcare setting, and an outline of a worker training program is developed to align with the noted best practices. The program overview presented is based on a competency-based framework and designed in a way such that it can be customised to required environmental circumstances. A practical health and safety training program application is outlined, showcasing adaptation in vocational education and training sector to a current context.